ASSESSMENT OF ATTITUDES AND PERCEPTIONS ON SUSTAINABLE NUTRITION PRACTICES AMONG STUDENTS IN SELECTED TERTIARY INSTITUTIONS IN ABEOKUTA, OGUN STATE, NIGERIA - Abdussalaam, Rukayat; Ranti-Oni, Oluwaferanmi E.; Abdulsalam, Basit Olawale (FUDMA JOURNAL OF SCIENCES, 2025)
Growing concerns about the health, environmental, and social consequences of food choices have led to a greater focus on sustainable nutrition. This study assessed the consumer behaviour and perceptions of sustainable nutrition practices among students in selected tertiary institutions in Ogun State, Nigeria. A total of 435 respondents participated in the survey, using a semi-structured questionnaire to collect data on socio-demographics, awareness, attitudes, consumption patterns, and perceived barriers towards sustainable nutrition. Findings show that 76.8% of respondents were aged 18–25 years. Only 44.8% had previously encountered the term “sustainable diet,” mainly through school (18.3%) or online sources (17.3%). While 39% reported considering sustainability in their food choices, 54.8% expressed a willingness to pay more for environmentally friendly products. Common practices included cooking to reduce left overs (64.5%) and buying locally sourced foods (65%), while avoiding imported foods was least observed (26.8%). Difficulty in changing habits (37%) was the most cited barrier. The study highlights a positive attitude towards sustainable nutrition among students, but also reveals limited awareness and behavioural gaps. Targeted nutrition education and institutional sensitisation are recommended to promote sustainable dietary behaviours among young adults in tertiary institutions
Keywords: Sustainable nutrition; Consumer behaviour; Food system